Navigating institutional logics: an ethnography of mental health peer support worker implementation - Charles, Ashleigh (2025)
Peer support worker (PSW) roles are increasingly implemented in mental health services in the United Kingdom. While existing studies suggest that organisational culture (OC) plays a pivotal role in shaping PSW implementation success, there is a lack of theoretical clarity regarding what constitutes OC in this context. To address this gap, this thesis applies the theory of institutional logics as one approach to exploring aspects of OC and its impact on PSW role implementation within a community mental health team. A qualitative ethnographic approach was employed, collecting data over a five-month period through four hundred and thirty-two hours of non-participant observation, thirteen semi-structured interviews, informal interviews, and sixty-eight documents and artefacts. To clarify what constitutes OC in relation to PSW implementation, this thesis highlights three intersecting and sometimes competing institutional logics: managerial, therapeutic, and professional. Time and risk were identified as key mechanisms that intersected with each logic, bringing their nuances into sharp focus and exposing areas of tension and alignment, influencing the implementation of the PSW. Time emerged as a critical mechanism affecting role boundaries and interactions, with the PSW facilitating swift, meaningful connections with service users, alleviating time pressures on clinicians, and enabling them to focus on tasks aligned with their expertise. Similarly, risk was reconceptualised, with the lived experience of PSW providing an alternative perspective on risk, enhancing overall risk management, and allowing clinicians to focus on their roles while relying on the PSW’s additional capacity for managing certain risk aspects. Three processes were used to navigate competing institutional logics, including (1) eliminating, (2) reframing, and (3) reassigning. Despite challenges relating to the limited number of PSWs, the findings suggest that PSWs can help mitigate broader systemic constraints, particularly in austerity-impacted environments. This thesis is the first to apply institutional logics to PSW implementation, offering an in-depth theoretical understanding of how aspects of OC influence this integration. Two key recommendations are proposed: (1) organisations should develop clear guidelines that outline how PSWs may operate differently to other team members, in order to maintain the integrity of the PSW role and ensure their unique contributions - especially in relation to risk and time - are recognised and effectively utilised, and (2) managers should be trained to understand when and how to adapt team processes to support PSWs, fostering a collaborative environment that enhances their cross-team impact. This thesis contributes new theoretical insights into PSW role implementation and provides guidance for policymakers, clinicians, and organisational leaders to enhance the impact, sustainability, and contributions of PSWs in mental health services.